Dynamics for Satisfaction with Telecom Services : A Pragmatic Investigation on Customers of Bhopal, Madhya Pradesh - Yadav, Rajesh K.; Dabhade, Nishant (Indian Journal of Marketing, 2019)
This research study was an effort to ascertain some implicit factors that influenced customer satisfaction in the Indian mobile service industry. Various satisfaction measures like communication services, network issues, technology, price, brand image, and customer care services were analyzed. With the introduction of Reliance Jio in December 2015, the Indian telecom market got distracted and stimulated in Madhya Pradesh as Jio offered various free communication services, lower data packs, and free voice calls without roaming. This step of Reliance Jio created a cold war among the mobile service provider firms and put immense pressure on competitors to offer similar services at comparatively lower prices. With the market moving forward, customer satisfaction has become mandatory for service providers to stay competitive in the market. This research study was exploratory in nature. Primary data were collected through a questionnaire from 500 mobile service users. Factor analysis was employed to analyze the data through SPSS 21.0 software, which was randomly collected from Bhopal (M.P.), India. Ten factors were identified out of 32 items of seven variables. The findings showed that diversity of plans and quality of network signals were two important foretellers of customer satisfaction in the mobile service industry.